An International Survey of Front-end Receivers and Observing Performance of Telescopes for Radio Astronomy. (2nd July 2019) - Bolli, P.; Orfei, A.; Zanichelli, A.; Prestage, R.; Tingay, S. J.; Beltrán, M.; Burgay, M.; Contavalle, C.; Honma, M.; Kraus, A.; Lindqvist, M.; Perez, J. Lopez; et al.
Abstract: This paper presents a survey of microwave front-end receivers installed at radio telescopes throughout the world. This unprecedented analysis was conducted as part of a review of front-end developments for Italian radio telescopes, initiated by the Italian National Institute for Astrophysics in 2016. Fifteen international radio telescopes have been selected to be representative of the instrumentation used for radio astronomical observations in the frequency domain from 300 MHz to 116 GHz. A comprehensive description of the existing receivers is presented and their characteristics are compared and discussed. The observing performances of the complete receiving chains are also presented. An overview of ongoing developments illustrates and anticipates future trends in front-end projects to meet the most ambitious scientific research goals.